Core microbiota for nutrient digestion remained and ammonia utilization increased after continuous batch culture of rumen microbiota in vitro - Liu, Mengyu; Wang, Tong; Wang, Lu; Xiao, Hanjie; Li, Jinhui; Duan, Chunhui; Gao, Lijie; Liu, Yueqin; Yan, Hui; Zhang, Yingjie; Ji, Shoukun (Frontiers in Microbiology, 2024)
Introduction This study aimed to investigate the digestive function, urea utilization ability, and bacterial composition changes in rumen microbiota under high urea (5% urea in diet) over 23 days of continuous batch culture in vitro. Methods The gas production, dry matter digestibility, and bacterial counts were determined for the continuously batch-cultured rumen fluid (CRF). The changes in fermentation parameters, NH3-N utilization efficiency, and microbial taxa were analyzed in CRF and were compared with that of fresh rumen fluid (RF), frozen rumen fluid (FRF, frozen rumen fluid at −80°C for 1 month), and the mixed rumen fluid (MRF, 3/4 RF mixed with 1/4 CRF) with in vitro rumen fermentation. Results The results showed that the dry matter digestibility remained stable while both the microbial counts and diversity significantly decreased over the 23 days of continuous batch culture. However, the NH3-N utilization efficiency of the CRF group was significantly higher than that of RF, FRF, and MRF groups (p < 0.05), while five core genera including Succinivibrio, Prevotella, Streptococcus, F082, and Megasphaera were retained after 23 days of continuous batch culture. The NH3-N utilization efficiency was effectively improved after continuous batch culture in vitro, and Streptococcus, Succinivibrio, Clostridium_sensu_stricto_1, p.251.o5, Oxalobacter, Bacteroidales_UCG.001, and p.1088.a5_gut_group were identified to explain 75.72% of the variation in NH3-N utilization efficiency with the RandomForest model. Conclusion Thus, core bacterial composition and function retained under high urea (5% urea in diet) over 23 days of continuous batch culture in vitro, and bacterial biomarkers for ammonia utilization were illustrated in this study. These findings might provide potential applications in improving the efficiency and safety of non-protein nitrogen utilization in ruminants.